Comparative and phylogenetic analyses of plastid genomes of the medicinally important genus Alisma (Alismataceae) - Lan, Zhi-Qiong; Zheng, Wen; Talavera, Alicia; Nie, Ze-Long; Liu, Jing; Johnson, Gabriel; Yin, Xian-Mei; Zhao, Wen-Qi; Zhao, Zong-Yi; Handy, Sara M.; Wen, Jun (Frontiers in Plant Science, 2024)
Alisma L. is a medicinally important genus of aquatic and wetland plants consisting of c. 10 recognized species. However, largely due to polyploidy and limited taxon and gene sampling, the phylogenomic relationships of Alisma remain challenging. In this study, we sequenced 34 accessions of Alismataceae, including eight of the ten species of Alisma, one species of Echinodorus and one species of Luronium, to perform comparative analyses of plastid genomes and phylogenetic analyses. Comparative analysis of plastid genomes revealed high sequence similarity among species within the genus. Our study analyzed structural changes and variations in the plastomes of Alisma, including IR expansion or contraction, and gene duplication or loss. Phylogenetic results suggest that Alisma is monophyletic, and constitutes four groups:(1) A. lanceolatum and A. canaliculatum; (2) the North American clade of A. subcordatum and A. triviale; (3) A. wahlenbergii and A. gramineum; and (4) A. plantago-aquatica from Eurasia and northern Africa with the eastern Asian A. orientale nested within it. Hence the results challenge the recognition of A. orientale as a distinct species and raise the possibility of treating it as a synonym of the widespread A. plantago-aquatica. The well-known Alismatis Rhizoma (Zexie) in Chinese medicine was likely derived from the morphologically variable Alisma plantago-aquatica throughout its long history of cultivation in Asia. The plastome phylogenetic results also support the tetraploid A. lanceolatum as the likely maternal parent of the hexaploid eastern Asian A. canaliculatum.